EFEKTIVITAS PENGGUNAAN DANA DESA DAN PENGARUHNYA TERHADAP TINGKAT KEMISKINAN DI KABUPATEN ACEH BARAT - Alvia Sabira; Syahril Syahril; Bukhari Bukhari (Universitas Teuku Umar, 2021)
This study aims to determine the effect of DDS and DDN on poverty levels in West Aceh. The data used in this study is secondary data from 2015-2020 sourced from SIPEDE (village development information system) and BPS (central statistical agency). The model used is multiple linear regression with analysis method using OLS (ordinary least square) parameter estimation approach. The results showed that the independent variable DDS (sapras village funds) had a positive and insignificant effect on TKM (poverty level), while the independent variable DDN (non-sapras village funds) had a significant negative effect on TKM (poverty level). The value of the coefficient of determination (R²=0.8106) shows that the poverty rate of West Aceh of 81.06 percent is influenced by DDS and DDN, and more than 18.94 is influenced by other variables outside this research.Future recommendations for the central government are to increase the Village Fund so that Sapras and Non-Sapras activities are maximized for village development. And prioritize non-Sapras activities in the field of community empowerment and training. Keywords: DDS, DDN, TKM